Process and mechanism modeling of cefotaxime removal from hospital wastewater using pistachio shells based magnetic activated carbon nanoparticles - Atefeh Rahmani; Haripriya Naidu; Tomasz Świergosz; Hamid Reza Rahimi; Zahra Mousavi; Maryam Dolatabadi; Saeid Ahmadzadeh (Scientific Reports)
Abstract Antibiotic residues have been extensively identified in diverse aquatic environments, posing significant health risks to both humans and animals, while also presenting challenges to the environment. Consequently, the imperative need to effectively removal antibiotics from the environment has become a very importance issue. In this study, response surface methodology with central composite design was employed to systematically investigate the effects of key process parameters, on the removal of cefotaxime (CTX) from hospital wastewater using pistachio sells based activated carbon modified with FeCl3. The modified activated carbon was synthesized using a thermochemical method and characterized by analytical techniques including FE-SEM, FTIR, XRD, pHpzc, and BET analysis, which demonstrated its remarkable physicochemical properties. Maximum removal efficiency of 99.1% was obtained via the optimal values of 45 mg L− 1 of initial CTX concentration, solution pH 7, and 200 mg L− 1 of Fe@ACP dosage, 56 min of reaction time through adsorption process. According to the results, the non-linear Langmuir isotherm model (R2 = 0.9931) and non-linear second order kinetic model (R2 = 0.9934) are suitably described the monolayer and chemisorption of CTX adsorption. The maximum adsorption capacity of Fe@ACP is 651.6 mg g− 1. Consequently, the developed treatment process revealed successful performance for quick and efficient removal of CTX by Fe@ACP. The developed process introduced an economic and green approach for the comprehensive utilization of agricultural waste resources used for environmental pollution control.